Toward miniaturizing microelectronics using covalent organic framework dielectric - Wiraja, Christian (2022)
As miniaturization of microelectronics reaches sub-10 nm scale, signal crosstalk and parasitic resistive-capacitive delay significantly limit device performance. While low dielectric constant (low-κ) dielectrics are widely recognized to address such issue, their poor thermal conductivity impedes heat management. Recently, scientists from Northwestern University and University of Virginia demonstrated the fabrication of pristine covalent organic framework (COF) thin films as a thermally conducting low-κ dielectric. Specifically, reported COF-5 film complements low-κ dielectric value (κ = 1.6) with high thermal conductivity (1 W m-1 K-1), offering promising adaptations in microelectronics with high power density.